«THE PROBLEM OF SYMBOLIC MEANINGS DIFFERENTIATION OF TERMS «COMMUNICATIVE» AND «COMMUNICATIONS» - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article deals with philosophical analysis of communicative phenomena in the context of modern scientific narratives development.